KECERDASAN KOMPREHENSIF DALAM PEMBELAJARAN FISIKA SISWA KELAS X SMA - Heni Nofira; Hamdi Rifai; Zulhendri Kamus (PILLAR OF PHYSICS EDUCATION, 2015)
One of factor causes low learning outcomes is using of student worksheets that do not support the achievement of all the competence of both aspects of knowledge, spiritual attitude, social attitude, and skills. The purpose of this research is  to investigate the impact of student worksheets containing comprehensive intelligence to physics learning outcomes in X grade SMA Pembangunan Laboratorium UNP. The type of this research is quasi experiment research with randomized control group only design. The population of this research is all students of X MIA grade SMA Pembangunan Laboratorium UNP in the first semester of academic year 2014/2015. Sampling technique is total sampling. The  research’s  instrument are test sheet (multiplier choice) for knowledge, observation sheet for spiritual and social attitude, and performance  rubric  for  skills.  The result of this research showed that  the  mean  score  of  the experiment class is higher than control class. The  result of research states  that  there  is  effect of implementation worksheet students containing comprehensive intelligence to physics learning outcomes in X MIA grade SMA Pembangunan Laboratorium UNP with 0,05 significance level